Geoecologia das paisagens na bacia hidrográfica do rio Gramame-PB com auxílio de sensoriamento remoto e sistemas de informações geográficas - Teódulo, José Mácio Ramalho (2014)
Understanding the characteristics structure and function of a landscape requires the accomplishment of studies at different spatial and temporal scales The Landscape Ecology has established itself as an interdisciplinary research field that offers theoretical and methodological framework for dealing with environmental problems Environmental changes resulting from human activities such as deforestation industrial growth and urban cluttered can modify the spatial pattern and rhythms of ecological processes within a landscape The current technological development has increased the ability to analyze and better manage global landscapes accordingly making use of holistic and geosystem approaches the theoretical and methodological framework of this research are supported by the Landscapes Ecology and aimed to utilize features of geotechnology to identify define and place them in its landscape units within the watershed of Gramame river located on the southern coast of Paraíba state covering a total area of 591 63 km² We seek to evaluate how is the geoecological dynamics at the regional scale (1:150.000) and local (1:15.000) and with that submit proposals to management of these areas We accomplished data collection in the field and office and analysis of the dynamics structure and functioning of the geosystem involved The modeling of the landscape was performed based on data obtained by remote sensing processing handling and analysis of spatial data by using GIS techniques (Geostatistics Digital Image Processing) and Geographic Information Systems (GIS) which is permitted presents them cartographically The results reveal an intensively altered landscape with the natural vegetation reduced to small and isolated fragments surrounded by agricultural crops the greatest human pressure of the study area corresponds to the lower course of the Gramame river where urban occupation is made by undisciplined and without environmental planning. The excessive use of pesticides industrial chemicals fertilizers intensive agricultural mechanization and the suppression of natural vegetation cover favor the proliferation of pests contamination of water resources habitat fragmentation and biodiversity loss The cartographic modeling and landscape metrics proved to be essential for the understanding of climatic soils geological geomorphological ecological and socioeconomic processes as well as the dynamics and evolution of the landscape.